The Effect of Budgeting Quality and Human Resource Competency of School Financial Performance with Information Technology as a Moderating Variables - Fauzan, Slamet; Dian Wisika Prajanti, Sucihatiningsih; Wahyudin, Agus (Universitas Negeri Semarang, 2019)
This research was conducted to identity the influence of budget quality and financial human resources competence on the school financial performance. In addition, this research was conducted to identity the influence of moderating variables of information technology on the relationship between budget quality and human resources competence on the school financial performance. This research is population research. The number of population in this research is among all the vocational haigh school in Pemalang Regency with totaling 42 schools. Of the 42 schools, only 37 schools who returned the questioners. This research used quantitative approach using hypothesis testing study design. To test hypothesis using multiple linier regression analysis with the absolute different with application program SPSS. The result of analysis shows that quality of budgeting, financial human resources competence on the school and information system have a positive significant effect on the school financial performance with simultanely or partially. information technology has a positive significant effect in moderating the influence of budget quality on school financial performance. However, information technology have not significant effect in moderating the influence of budget quality on school financial performance